2022
DOI: 10.3390/cells12010001
|View full text |Cite
|
Sign up to set email alerts
|

Lower Metabolic Potential and Impaired Metabolic Flexibility in Human Lymph Node Stromal Cells from Patients with Rheumatoid Arthritis

Abstract: Cellular metabolism is important for determining cell function and shaping immune responses. Studies have shown a crucial role for stromal cells in steering proper immune responses in the lymph node microenvironment. These lymph node stromal cells (LNSCs) tightly regulate immune tolerance. We hypothesize that malfunctioning LNSCs create a microenvironment in which normal immune responses are not properly controlled, possibly leading to the development of autoimmune diseases such as rheumatoid arthritis (RA). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…These lipofuscin granules contain highly oxidized proteins, mostly unsaturated fatty acids, that cannot be removed by proteasomal degradation and accumulate in lysosomes with age (40, 41). We previously showed increased ROS production by RA LNSCs (42) and here we observed significantly more lipofuscin granules already in RA-risk LNSCs. In aggregate, this indicates that detected autofluorescence in RA(– risk) LNSCs may reflect increased lysosomal content and oxidative stress.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…These lipofuscin granules contain highly oxidized proteins, mostly unsaturated fatty acids, that cannot be removed by proteasomal degradation and accumulate in lysosomes with age (40, 41). We previously showed increased ROS production by RA LNSCs (42) and here we observed significantly more lipofuscin granules already in RA-risk LNSCs. In aggregate, this indicates that detected autofluorescence in RA(– risk) LNSCs may reflect increased lysosomal content and oxidative stress.…”
Section: Discussionsupporting
confidence: 78%
“…CD38 levels inversely correlate with the age-related decline in nicotinamide adenine dinucleotide (NAD), which ultimately leads to mitochondrial dysfunction and metabolic alterations (45, 46). It is interesting to postulate that our earlier detected metabolic alteration in LNSCs (42) is related to altered CD38 and NAD+ levels. Additional research is needed to investigate whether the differential expression of these genes are causative related to the observed senescence phenotype of RA LNSCs and may guide future studies aimed at restoring LNSC function.…”
Section: Discussionmentioning
confidence: 86%
“…While our study also cannot definitively establish whether the SARS-CoV-2 vaccine directly worsened RA, it is possible that mRNA vaccination could serve as an aggravating factor in RA as, for instance, smoking, obesity and environmental factors might ( 19 ). Recent study has shown the distinct different metabolic alterations of local lymph node stromal microenvironment in RA patients compared with healthy controls ( 20 ). Thus, the present result suggests that for some RA patients, the SARS-CoV-2 vaccine might act as a potential trigger for exacerbation of arthritis compared with healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In our dataset, CCL19+ SCs express high levels of CCL2 in the vessel-rich areas of the T cell zone where they might attract monocytes, as previously described in FRCs dwelling the T cell zone 34 . Furthermore, it is worth noting that LNSC predominantly rely on fatty acid metabolism 35 . This is evident through the high expression in CCL19+ SCs of CD36, FABP4, and FABP5, proteins that play crucial roles in the fatty acid metabolism 36 , FABP4 and FABP5 also are involved in the maintenance of T lymphocyte homeostasis through the modulation of cytokine production in thymic stromal cells 37 .…”
Section: Ccl19+ and Ccl21+ T Cell Area Fibroblast Reticular Cellsmentioning
confidence: 99%